2019
DOI: 10.1186/s12981-019-0219-1
|View full text |Cite
|
Sign up to set email alerts
|

Moderate prevalence of HIV-1 transmitted drug resistance mutations in southern Brazil

Abstract: BackgroundDespite the advances in therapy, the occurrence of drug-resistant human immunodeficiency virus type 1 (HIV-1) is a major obstacle to successful treatment. This study aimed to characterize the genetic diversity and to determine the prevalence of transmitted drug resistance mutations (TDRM) between individuals recently or chronically diagnosed with HIV-1 from Paraná, Brazil.MethodsA total of 260 HIV-1 positive antiretroviral therapy-naïve patients were recruited to participate on the study, of which 39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
4
7
1
4
Order By: Relevance
“…Similarly, a study done in Brazil among ART-naive pregnant women indicated a lower PDR detection rate [ 24 ]. In addition to the above previously published data from Ethiopia, this finding is in agreement with studies done in India [ 25 ], Brazil [ 26 28 ], China [ 29 ], and Iran [ 30 ], which reported a moderate magnitude of PDR among HIV-1 antiretroviral adults. The absence of PDRM screening before starting ART and poor level of adherence might have contributed to this increment of PDR in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, a study done in Brazil among ART-naive pregnant women indicated a lower PDR detection rate [ 24 ]. In addition to the above previously published data from Ethiopia, this finding is in agreement with studies done in India [ 25 ], Brazil [ 26 28 ], China [ 29 ], and Iran [ 30 ], which reported a moderate magnitude of PDR among HIV-1 antiretroviral adults. The absence of PDRM screening before starting ART and poor level of adherence might have contributed to this increment of PDR in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the prevalence of primary resistance among ART-naive Iranian patients (8.3%) was lower than that of many other countries [Germany (17.2%) [23], Greece (16.9%) [24], Brazil (13.3%) [25], and France (10.8%) [26]], but it seems to be rising when compared to previous reports from Iran [11,19,20,27].…”
Section: Parametercontrasting
confidence: 81%
“…Acquired and transmitted DRM remain one of the major obstacles towards ART efficacy and AIDS treatment. In case of Brazil, previous regional studies showed distinct moderate patters of transmitted DRM prevalence [ 11 , 16 , 20 , 27 , 38 ], and high DRM rates in patients receiving ART [ 17 , 18 , 19 , 27 , 39 ]. In this study, we aimed at understanding SDRM [ 26 ] prevalence across the 27 Brazilian federative units focusing on 20,226 HIV-1 infected patients under different ART schemes, with viral sequence genotyped between 2008 and 2017.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of DRM can greatly vary between different geographical areas, depending on several factors, ranging from study design to the sociodemographic characteristics of the population and most prevalent HIV-1 subtypes [ 9 , 11 , 12 , 13 , 14 , 15 ]. With a total area as vast as 8.51 million km 2 , different DRM rates have also been found in distinct Brazilian geographic regions [ 9 , 12 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%